Varsaviana Kazimierza Pątka / [Zbigniew Dolatowski]. - Dolatowski, Zbigniew (1927-2001) (1981)
W ozdobnym obramowaniu Syrenka Warszawska, napis w półkolu: Varsaviana. Kazimierza. Pątka. Sygn. aut. w obrębie kompoz.